VIDEO BLOG (VLOG) SISTEM REPRODUKSI SEBAGAI MEDIA PEMBELAJARAN BIOLOGI - Utami, Anin septi Aziz; Chodzirin, Muhamad; khasanah, Nur (Jurnal BIOEDUIN, 2019)
Global demands require the world of education to always develop technology in an effort to improve education, promote the use of information and communication technology for the world of special education in the learning process. The use of technology media that is done correctly will be able to make learning activities and obtain information and knowledge more effective and efficient. This study aims to produce a product that consists of vlog (video blog) -based learning media in the payment system material for free socialization material. This type of research is Research and Development (R & D), using the ADDIE Model (Analysis, Design, Develop, Implement, Evaluate). Before the product is developed, a scenario is first made. After the product is developed it is validated by material experts, media experts and biology teachers, then implement to students. The subjects of this study were 32 students from XI MIPA class SMA N 2 Slawi and 17 students from class XI MIPA MA Uswatun Hasanah. The validation test results show that the vlog (blog video) is suitable for use with the appropriate revision of the advice given The percentage of eligibility of material experts is 79%, media experts are 85%, biology teachers are 84% and students are 88%.